Performance measurement and incentive systems in purchasing : More than just savings - Hofmann, Erik (Professional Supply Management, 2014)
In recent years, purchasing performance measurement have steadily gained in importance in theory and practice. Yet, in many cases, the focus still remains on cost items, especially savings. Moreover, reported performance ratios in purchasing are frequently called into question in terms of their amount and efficacy. Most of the time, there is no tie-in at all with staff compensations. To meet these and other challenges, this book presents a holistic approach for purchasing performance measurement and the incentive systems associated with it. The following topics are dealt with in detail: • Purchasing performance measurement on the level of commodity groups and the procurement organization • Supplier evaluation and performance measurement on the level of the buyer-supplier relationship • Comprehensive systems for purchasing performance measurement, such as the procurement value added and the purchasing balanced scorecard • Performance-oriented incentive systems and bonus payments for buyers, procurement organizations and suppliers Readers are thus provided with comprehensive guidelines for the implementation and realization of sustained performance measurement and incentivization in purchasing.